132 Investigating the lowest threshold of vascular benefits from LDL lowering with a PCSK9 inhibitor in healthy volunteers – results from the intensity-low study. (17th July 2020) - Cacciottolo, Paul; Kostapanos, Michalis S; Pavey, Holly; Hubsch, Annette; Wilkinson, Ian B; Cheriyan, Joseph
Abstract : Background: There is a continuous relationship between low density lipoprotein cholesterol (LDL-C) and cardiovascular risk. The cardiovascular benefits of reducing LDL-C in low risk normocholesterolaemic subjects is unknown. The INTENSITY LOW study sought to determine whether lowering LDL-C by alirocumab improves endothelial function in healthy individuals. Method: This was a single-centre, randomised, single-blind, placebo-controlled study. 30 healthy normocholesterolaemic participants aged 18-45 were randomized 1:1 to receive either alirocumab 150mg or placebo subcutaneously. Forearm blood flow (FBF) as measured by venous occlusion plethysmography was undertaken at baseline and again after 2 weeks therapy. Endothelium-dependent and -independent vasodilation were assessed during intra-arterial infusion of acetylcholine (ACh) and sodium nitroprusside (SNP) respectively. All participants then received a further dose of their original treatment allocation, as well as atorvastatin 20mg once daily, and measurements were undertaken after a further 2 weeks. Pulse wave velocity (PWV), Augmentation Index (AIx) and carotid Intima-media thickness (CIMT), as well as LDL-C levels, were measured at each timepoint. Results: Alirocumab reduced LDL-C compared to placebo by 48% (ΔLDL-C -1.00mmol/L, 95% CI 0.89-1.11, P<0.001). There was no difference in endothelium-dependent forearm responses to ACh between alirocumab and placebo (ΔFBF response 5.13 ml(100ml)-1min-1, 95% CI 4.07 -6.19, P=0.977). However, forearm ACh responses improved when comparing alirocumab + atorvastatin to atorvastatin alone (ΔFBF response 8.06 ml(100ml)-1min-1, 95% CI, 7.06-9.06, P=0.01). There was no significant change in endothelium-independent responses to SNP when comparing alirocumab to placebo (ΔFBF response 5.85ml(100ml)-1min-1, 95% CI 4.88 – 6.82, P=0.462), or alirocumab + atorvastatin to atorvastatin alone (ΔFBF response 6.00ml(100ml)-1min-1, 95% CI 5.07 – 6.93, P=0.389). There was no significant change in PWV with alirocumab therapy (ΔPWV -0.271 ± 0.223 ms-1, P=0.271), or with the addition of statin to alirocumab therapy (ΔPWV 0.073 ± 0.23ms-1, P=0.753). There was no significant change in AIx with alirocumab therapy (ΔAIx -1.143 ± 2.884, p=0.692) or with the addition of statin to alirocumab therapy (ΔAIx -4.203 ± 4.102, p=0.306). CIMT was reduced with alirocumab therapy (ΔcIMT –0.051 ± 0.026mm, p=0.05), but there was no significant change with addition of statin to alirocumab therapy (ΔcIMT –0.005 ± 0.031mm, p=0.882). Conclusion: Alirocumab significantly reduced LDL-C compared to placebo without any change to endothelial function, as measured by forearm plethysmography, or to markers of arterial stiffness, as measured by PWV and AIx, in normocholesterolaemic healthy subjects. However, an improvement in endothelial function was seen when combination therapy was compared to statin therapy alone. Conflict of Interest: None